UPAYA MENINGKATKAN PEMAHAMAN KONSEP MEMBACA SUKU KATA MELALUI METODE KOOPERATIF TYPE NHT BERBANTUAN MEDIA GAMBAR SISWA SDN SUMURGEDEI KECAMATAN CILAMAYA KULON KABUPATEN KARAWANG - Nurhayati; Prima Danu Astri Susanti; Muhammad Arif (JURNAL ARMADA PENDIDIKAN, 2023)
The purpose of this study was to increase understanding of the concept of reading syllables with the NHT type cooperative method assisted by media images in the hope that students' reading comprehension of syllables would increase. This type of research is Classroom Action Research which consists of 2 improvement cycles with four stages namely, planning, implementing, observing, and reflecting. The research subjects were class I students at SDN Sumurgede I with a total of 26 students, including 19 male students and 17 female students. The implementation of the first cycle of student completeness was 38.19% and increased in the improvement of the second cycle with student mastery of 95.44%. Based on the results of this study, it can be concluded that the NHT-type Cooperative method assisted by media images can improve the reading syllable concepts of class I SDN Sumurgede I SDN Cilamaya Kulon District, Karawang Regency semester II in the 2022/2023 academic year.